Percepción del alumno de Estomatología de la Universidad Nacional de Trujillo sobre la educación a distancia en pandemia - 2022 - Julián Guevara, Ana Flor De María (2023)
The COVID-19 pandemic has generated a great change in education due to social distancing, with our profession being one of the most affected by the impossibility of clinical care and management of patients both professionally and in the training of dental students. The purpose of this study was to evaluate the perception of the student of the Faculty of Stomatology of the National University of Trujillo about distance education in times of pandemic in the year 2022. This research is basic, descriptive and non-experimental. The population consisted of 124 students from the first to the sixth year of the UNT Stomatology Faculty, enrolled during the 2022 academic cycle. The instrument used was a questionnaire applied Google forms with the prior completion of informed consent.It was found that the perception of distance education in times of pandemic is good in 57.8% of the students. Likewise, the six academic years reported a good perception, the academic year being significantly associated with the perception of distance education (p=0.013). The female gender predominated among the students surveyed, 60% of women and 51.5% of men had a good perception, however, gender was not associated with the perception of distance education (p=0.528).It is concluded that the perception of the student of the dental school of the National University of Trujillo on distance education in times of pandemic is good